Comparison between auditory and visual simple reaction times and its relationship with gender in 1st year MBBS students of Jawaharlal Nehru Medical College, Bhagalpur, Bihar - Arohi Abhinav Jayaswal (International Journal of Medical Research and Review, 2016)
Objective: This study was to find out whether the simple reaction time was faster for auditory or visual stimulus. And also whether there is any relationship between Reaction time and gender of an individual.Methodology: 32 first year M.B.B.S. students were divided randomly into 2 groups each consisting of 16 male students and 16 female students. Both the groups were performed for the visual and auditory tests. The tests were taken from the Direct RT software program from a laptop. The Direct RT software consists of Test lab visual and Test lab sounds to test the reaction times to visual and auditory stimuli. For each group both the visual and auditory reaction time test were conducted and, the data was taken. The mean reaction time was calculated excluding the first and last values.Results: The results shows that the mean visual reaction time is around 293.37± 13.01 milliseconds as compared to the mean auditory reaction time of around 248.61 ±12.84 milliseconds. The mean visual reaction time is 285.59±12.53 milliseconds in males and 301.15±13.49 milliseconds in females. The mean auditory reaction time is 246.88±14.33 milliseconds in males and 250.35±11.36 milliseconds in females.Conclusion: This shows that the auditory reaction time is faster than the visual reaction time. And also males have faster reaction times when compared to females for both auditory as well as visual stimuli.